Uji Toksisitas Akut Oral Ekstrak Etanol Akar Tanaman Bungkus (Smilax rotundifolia L.) pada Tikus Putih Jantan (Rattus nervegicus) - Wulandari, Ayu; Patala , Recky; Mariyani , Mariyani; Prinasari , Rezan (Journal of Pharmaceutical and Sciences, 2025)
Background: Smilax rotundifolia, commonly known as "bungkus" plant, is an indigenous species from Papua recognized for its potential as an aphrodisiac agent. Traditionally, the local population applies parts of the plant directly to the male genital area, a method that causes itching and highlights the need for development into a safer and more user-friendly formulation. Objective: This study aimed to evaluate the safety of the ethanol extract of Smilax rotundifolia roots through acute toxicity testing, with observation parameters including signs of toxicity, body weight changes, and LD₅₀ value. Methods: Acute toxicity testing was conducted on male white rats (Rattus norvegicus) divided into five groups: normal control and treatment groups receiving extract doses of 5, 50, 300, and 2000 mg/kg body weight. Toxic signs were observed at 0; 0.5; 1; 2; 4; 6; and 24 hours post-administration, while body weight was monitored over a 14-day period. Results: No mortality was observed in any of the treatment groups up to day 14. The rats’ body weights did not show significant changes, and no notable macroscopic organ abnormalities were found, even in the group receiving the highest dose (2000 mg/kgBW). Conclusion: Based on these findings, the ethanol extract of Smilax rotundifolia root is classified as low toxicity (Category 5) or practically non-toxic.